Effect of Platelet-Rich Plasma on Peri-Implant Bone Repair: A Histologic Study in Dogs - Garcia, Ricardo V. [UNESP]; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Spolidorio, Luis C.; Padilha Filho, Joao G. [UNESP]; Doria Neto, Francisco A. [UNESP]; Gouveia de Cardoso, Luciana A.; Shibli, Jamil A. (Allen Press Inc, 2010)
The present study evaluated the effect of platelet-rich plasma (PRP) on pen-implant bone healing. A total of 9 mongrel dogs received 36 dental implants with sandblasted acid-etched surface in lower jaws in a split-mouth design: in the PRP group (n = 18 implants) the implants were placed in association with PRP, and in the control group (n = 18 implants) the implants were placed without PRP. Biopsies were obtained and prepared for histologic and histometric analysis after 15, 30, and 55 days of healing. The biopsies retrieved at 15 days showed delicate bone trabeculae formed by immature bone with presence of numerous osteoblasts for both groups. At 30 days the trabeculae presented reversal lines and evident lamellar disposition, where some thread spaces were filled by bone and dense connective tissue. At 55 days, bone healing was not altered in the control group, and histologic aspects were variable for the group treated with PRP. There was no significant difference between the groups for bone-to-implant contact (P > .05). PRP did not enhance bone formation around sandblasted acid-etched implants.
Keywords: platelet-rich plasma; osseointegration; dental implants; growth factors; bone repair